ECONOMIC OVERHEATING - ISWARDONO SARDJONO PERMONO (Journal of Indonesian Economy and Business (JIEB), 1997)
"Common causes of overheating directly traceable to cooling systems, are clogging or improper circulation of cooling air. Another cause of overheating is operations or excessive engine idling under extreme conditions of heat or altitute" (Lorry Johnson, Fix your Vb/fcauogen, the Good heart-MBcox Co, Ins 1983 pp. 239). Generally the term overheating is associated with car or motorised engines which have an excess of heat. In this case overheating is not about warming-up cars, since warming-up is done to keep a car working properly. Therefore overheating can be inferred as a problem to car engines as a result of malfunction in the circulation of cooling air, tuhich is signalled by excess engine head, ouer the warning line limit. This paper attempt to discuss "overheating" as a phenomenon in economics term.